Iodine vapor staining for atomic number contrast in backscattered electron and X‐ray imaging. Issue 12 (15th September 2014) - Boyde, Alan; Mccorkell, Fergus A.; Taylor, Graham K.; Bomphrey, Richard J.; Doube, Michael
ABSTRACT Iodine imparts strong contrast to objects imaged with electrons and X‐rays due to its high atomic number (53), and is widely used in liquid form as a microscopic stain and clinical contrast agent. We have developed a simple technique which exploits elemental iodine's sublimation‐deposition state‐change equilibrium to vapor stain specimens with iodine gas. Specimens are enclosed in a gas‐tight container along with a small mass of solid I2. The bottle is left at ambient laboratory conditions while staining proceeds until empirically determined completion (typically days to weeks). We demonstrate the utility of iodine vapor staining by applying it to resin‐embedded tissue blocks and whole locusts and imaging them with backscattered electron scanning electron microscopy (BSE SEM) or X‐ray microtomography (XMT). Contrast is comparable to that achieved with liquid staining but without the consequent tissue shrinkage, stain pooling, or uneven coverage artefacts associated with immersing the specimen in iodine solutions. Unmineralized tissue histology can be read in BSE SEM images with good discrimination between tissue components. Organs within the locust head are readily distinguished in XMT images with particularly useful contrast in the chitin exoskeleton, muscle and nerves. Here, we have used iodine vapor staining for two imaging modalities in frequent use in our laboratories and on the specimen types with which we work. It is likely to be equally convenient for a wide range of specimens, and for other modalities which generate contrast from electron‐ and photon‐sample interactions, such as transmission electron microscopy and light microscopy. Microsc. Res. Tech. 77:1044–1051, 2014. © 2014 The Authors. Microscopy Research Technique published by Wiley Periodocals, Inc.